NAIKNYA BIAYA REKENING LISTRIK UNIVERSITAS TADULAKO TAHUN 2012 - Mukhlis, Baso (MEKTEK, 2012)
The amount of electricity bill payment of Universitas Tadulako in recent months has increased to between Rp. 240.000.000,- and Rp. 260.000.000,- per month. This bill payment increases three times compared by the average of electricity bill payment in period 2009 - 2010. Based on the monitoring and measurement results of the electricity load in surrounding Universitas Tadulako, it is found that the increasing of the electricity bill payment is caused by the unbalancing of the load consumption pattern such that resulting in lots of losses, so many electricity consumption in out of the work hours and there is a substation that uses the government group electricity rates which should use social group electricity rates.